Fuzzy Systems: An Approach to 5G Networks Under the SDN Paradigm - Albarracin Sanchez, Luis Felipe; Puerto Leguizamón, Gustavo Adolfo (Revista Científica, 2018)
The exploitation that has had the fuzzy systems related to advances of 5G networks (Fifth Generation Mobile Networks) and how this development has been framed by the paradigm of SDN (Software Defined Networks) architectures are reviewed in this article. The first part will review terms required for understanding the technologies and their evolution; on which different scenarios are evaluated because they have contributed to the development of the definition of 5G networks. Following, the research and development of the fuzzy systems applied to telecommunications, specifically 5G technology and SDN architectures will be described. Finally, the respective conclusions of the fuzzy systems in the 5G networks and SDN architectures will be exposed.